M12 TRPV1 polymorphism in chronic cough: no evidence for an effect on objective measurements of cough. (15th November 2016) - Turner, RD; Bourne, E; Mein, CA; Birring, SS; Shaheen, SO; Bothamley, GH
Abstract : Introduction and objectives: The afferent receptor TRPV1 is implicated in the cough reflex. Several single nucleotide polymorphisms (SNPs) in TRPV1 appear to be associated with symptoms of cough in the general population. 1 We investigated whether such SNPs are associated with the objective measures of cough reflex sensitivity and 24-hour cough frequency (CF24) in chronic cough. Methods: Patients were recruited from a specialist cough clinic with cough >2 months' duration as the only or predominant symptom. Each underwent measurement of C5 (minimum concentration of capsaicin required to produce 5 coughs) and wore the Leicester Cough Monitor for 24 h. Saliva samples were taken to extract DNA and genotype six SNPs of TRPV1 : rs161365, rs17706630, rs2277675, rs222741, rs150854 and rs224498. Mean values of C5 and CF24 were compared across genotypes and univariate linear regression was used to analyse the per minor allele associations with each outcome for each SNP, on the assumption their effects would be additive. 1 Results: 57 patients were recruited with underlying diagnoses including unexplained chronic cough (n = 43), asthma (n = 7) and gastro-oesophageal reflux (n = 2). 42 (74%) were female, and median (IQR) age and duration of cough was 60 (54–66) years and 5 (3–12) months, respectively. Median (IQR) C5 was 7.8 (3.9–15.6) μM/L and cough frequency 399 (181–651) coughs/24 h. Genotype frequencies were as shown (Table). There was no evidence for an association between TRPV1 polymorphisms and C5 or CF24. This was the case regardless of diagnosis. Conclusion: This small study did not provide support for a large effect of TRPV1 polymorphism on cough frequency or cough reflex sensitivity in chronic cough. However, we lacked power to detect small/modest effects. Reference: Smit, et al . Respir Res 2012;13 :26.